Global incidence, prevalence and features of primary sclerosing cholangitis: A systematic review and meta‐analysis. (19th July 2021) - Mehta, Tej I.; Weissman, Simcha; Fung, Brian M.; Sotiriadis, John; Lindor, Keith D.; Tabibian, James H.
Abstract: Background & Aims: Primary sclerosing cholangitis (PSC) is an idiopathic, cholestatic liver disease with a diverse range of clinical manifestations. Inter‐regional data on PSC are variable, but its global geoepidemiology has not been well‐studied. We aimed to examine the worldwide incidence, prevalence and features of PSC and PSC‐inflammatory bowel disease (PSC‐IBD). Methods: A systematic search of multiple databases was conducted to identify all original, full‐text studies until December 2020 with data regarding the incidence rate (IR) and/or prevalence of PSC. Outcomes were PSC IR, prevalence, features and IBD concurrence. Additionally, a meta‐analysis of PSC IR was performed. The study was registered in PROSPERO (CRD42021224550). Results: Of the 1003 studies identified, 17 studies spanning three continents were included. PSC IR was 0.60 per 100 000 person‐years (PY) (95% confidence interval: 0.37‐0.88 per 100 000 PY). In pooled subgroup analysis for studies conducted in Europe and North America, PSC IR was 0.62 and 0.53 per 100 000 PY, respectively. PSC prevalence ranged 0‐31.7 per 100 000 persons, with notable inter‐regional differences. Mean age at PSC diagnosis was bimodally distributed, with relative peaks at 15 and 35 years. Mean concurrence of IBD with PSC was 50%, with 76% having ulcerative colitis, 17% Crohn's disease and 8% indeterminate/unspecified IBD. Conclusion: While considerable heterogeneity exists in the geoepidemiology of PSC, overall, the classical dogmata of male predilection, bimodal distribution of mean age and high PSC‐IBD concurrence appear to hold true. Despite a seemingly stable IR over time, further studies are needed to better understand the geoepidemiology of PSC.